The deletion of six amino acids at the C-terminus of the alpha 1 (II) chain causes overmodification of type II and type XI collagen: further evidence for the association between small deletions in COL2A1 and Kniest dysplasia. Issue 8 (August 1996) - Winterpacht, A; Superti-Furga, A; Schwarze, U; Stöss, H; Steinmann, B; Spranger, J; Zabel, B
Abstract : We have identified an 18 bp deletion in exon 49 of the type II procollagen gene (COL2A1) in a patient with Kniest dysplasia. The deletion is located at the very C-terminus of the helical domain and removes two of three Gly-Pro-Pro triplets at positions 1007-1012, which are thought to be involved in helix formation and stability. Morphological investigation of an iliac crest biopsy showed large inclusions in the endoplasmic reticulum of chondrocytes, reflecting impaired secretion of type II collagen. Electrophoretic analysis of collagens extracted from cartilage or synthesised by cultured chondrocytes showed that type II and also type XI procollagen molecules containing mutant alpha 1 (II) chains showed post-translational overmodification. These observations provide further evidence for the general association of Kniest dysplasia with small deletions in the helical domain of type II collagen.